2002
DOI: 10.1111/j.1440-1584.2002.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Men Taking Their Rightful Place in Society? A Preliminary Analysis of a Participatory Action Research Process With Yarrabah Men's Health Group

Abstract: Men's groups are increasingly being accepted as an important strategy in improving health and wellbeing, especially in Indigenous communities. However, it is hard to find systematic documentation and evaluation of such initiatives in the literature. This paper analyses the formative stages of a participatory action research (PAR) process which aims to engage and support the members of the Yarrabah Men's Health Group plan, implement and evaluate their activities. Data for the paper are based on a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 2 publications
0
21
0
1
Order By: Relevance
“…From here the process itself is spiralling as knowledge and understanding informs strategy development, followed by action, reflection and new understanding with ongoing change and improvement being the goal. 7 Using this approach, our research partnerships with Indigenous organizations since 1988 have demonstrated powerful ways of working with and for Indigenous peoples' to be agents of their own change. 7Á9 This partnership between Indigenous and non-Indigenous researchers is importantly reflected through the composition of the research team, from the level of chief investigator through to community-based researcher.…”
Section: Participatory Action Researchmentioning
confidence: 98%
“…From here the process itself is spiralling as knowledge and understanding informs strategy development, followed by action, reflection and new understanding with ongoing change and improvement being the goal. 7 Using this approach, our research partnerships with Indigenous organizations since 1988 have demonstrated powerful ways of working with and for Indigenous peoples' to be agents of their own change. 7Á9 This partnership between Indigenous and non-Indigenous researchers is importantly reflected through the composition of the research team, from the level of chief investigator through to community-based researcher.…”
Section: Participatory Action Researchmentioning
confidence: 98%
“…A men's movement has emerged internationally, over the past four decades, which seeks to offer analyses of what has gone wrong for men and explore how this can be addressed. This movement has seen the establishment of a range of 'self-help' and 'self-improvement' initiatives, such as men's clinics, sheds, meetings and conferences, and the growth of men's support groups; since the 1990s, Aboriginal and Torres Strait Islander men have formed support groups designed to promote their own health and wellbeing and those of their communities (Tsey et al 2002). In 2002, there were 100…”
Section: Context and Literaturementioning
confidence: 99%
“…Factors associated with Aboriginal suicide are remarkably complex and almost always include intergenerational trauma, grief and loss (Australian Government, 2013) as well as obstacles to seeking help (Isaacs, Sutton, Hearn, Wanganeen, & Dudgeon, 2016). Furthermore, factors that may promote social and emotional well-being such as social connectedness and strengthening family bonds (Hunter & Milroy, 2006;Tsey, Patterson, Whiteside, Baird, & Baird, 2002) require a whole of community effort with substantial support from mainstream stakeholders.…”
Section: Ground Realities In Building Effective Aboriginal Suicide Prmentioning
confidence: 99%